Risk Mitigation of Disease Pandemic in the Indonesian Banking Industry: In Response to COVID-19 - Nikmah Mentari; Uni Tsulasi Putri (University of Jember, 2020)
As an intermediary institution, the banking industry plays a critical function in the economy. Unpredictable conditions such as disease pandemic, exemplified from the unprecedented COVID-19 outbreak, result in loss to the banking industry due to the weakening of the national economy. In the future, then, the banking industry requires early preventive action for a similar case through specific risk mitigation towards disease pandemic. This paper aims to discuss the urgency of the risk mitigation towards the pandemic in the banking industry, following the risk mitigation scheme in facing the pandemic with its relevant regulation. This paper shows that the pandemic's responsive risk mitigation has become essential to strengthen the banking’s intermediary function and performance during the pandemic. The existing risk mitigation regulation solely relates to the non-performing loan in normal conditions. In the meantime, disease pandemic like COVID-19 is excluded because it is beyond the normal situation. Its adverse impact has leveraged more significant extent due to emergency conditions. In case of a disease pandemic, the bank can soon take early preventive action before the pandemic strikes within the domestic territory without waiting for central government-specific regulation, but it should. However, it remains practiced under the relevant laws. KEYWORDS: Risk Mitigation, Disease Pandemic, COVID-19, Banking Industry, Indonesia.